2020
DOI: 10.1162/jocn_a_01535
|View full text |Cite
|
Sign up to set email alerts
|

Capture by Context Elements, Not Attentional Suppression of Distractors, Explains the PD with Small Search Displays

Abstract: Top–down control of attention allows us to resist attentional capture by salient stimuli that are irrelevant to our current goals. Recently, it was proposed that attentional suppression of salient distractors contributes to top–down control by biasing attention away from the distractor. With small search displays, attentional suppression of salient distractors may even result in reduced RTs on distractor-present trials. In support of attentional suppression, electrophysiological measures revealed a positivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(108 citation statements)
references
References 67 publications
6
99
3
Order By: Relevance
“…Thus, the electrophysiological results suggest that RTs to targets appearing at the same location as the inverted singleton cue were longer because attention was captured by the cue context and not because stimuli at the cued location were suppressed. In summary, the current study and Schönhammer et al (2020) demonstrate that signs of behavioral suppression do not always result from attentional suppression, despite the face value of this interpretation (see also Kerzel & Burra, 2020).…”
Section: No Evidence For Cue Suppressionmentioning
confidence: 49%
“…Thus, the electrophysiological results suggest that RTs to targets appearing at the same location as the inverted singleton cue were longer because attention was captured by the cue context and not because stimuli at the cued location were suppressed. In summary, the current study and Schönhammer et al (2020) demonstrate that signs of behavioral suppression do not always result from attentional suppression, despite the face value of this interpretation (see also Kerzel & Burra, 2020).…”
Section: No Evidence For Cue Suppressionmentioning
confidence: 49%
“…However, this interpretation of the P D has recently been challenged by results reported by Kerzel and Burra (2020). Using four-item search displays with a task-irrelevant color singleton similar to Gaspelin and Luck (2018a), but without interleaved probe trials, they confirmed the presence of an early positivity contralateral to a lateral color singleton in search displays where the target appeared on the vertical midline and thus did not elicit any lateralized ERP components.…”
Section: Introductionmentioning
confidence: 96%
“…The N2pc is triggered by search targets and other objects with targetdefining features, and is generally assumed to be a marker of the deployment of attention to these objects (Eimer, 1996;Luck & Hillyard, 1994a, 1994b. Kerzel and Burra (2020) interpreted the contralateral negativity triggered by color singleton distractors in their study as an N2pc reflecting attentional capture by these singletons. This pattern of results is difficult to reconcile with the idea that the preceding contralateral positivity (P D ) reflects active singleton suppression, since it is unclear why a singleton should still be able capture attention after it has been suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…Neither state nor trait anxiety correlated with RTs in any cueing condition, rs < .22, ps > .15. Kerzel and Burra (2020) proposed that, in small search displays, participants may systematically search lateral positions before vertical positions, even when the lateral item is a distractor. To examine this possibility, we compared RTs with lateral targets versus vertical targets in a 2 (Target Position) × 3 (Cue Type) repeated-measures ANOVA.…”
Section: Behavioralmentioning
confidence: 99%